Protective Role of Picralima nitida Seed Extract in High-Fat High-Fructose-Fed Rats - Opeyemi Christianah De Campos; Daniel Ikpomwosa Osaigbovo; Titilayo Ifeoluwa Bisi-Adeniyi; Franklyn Nonso Iheagwam; Solomon Oladapo Rotimi; Shalom Nwodo Chinedu (Advances in Pharmacological and Pharmaceutical Sciences)
Picralima nitida is a therapeutic herb used in ethnomedicine for the management of several disease conditions including diabetes. This study examined the potential palliative effect of aqueous seed extract of Picralima nitida (APN) on dyslipidemia, hyperglycemia, oxidative stress, insulin resistance, and the expression of some metabolic genes in high-fat high-fructose-fed rats. Experimental rats (2 months old) were fed a control diet or a high-fat diet with 25% fructose (HFHF diet) in their drinking water for nine weeks. APN was administered orally during the last four weeks. Anthropometric and antioxidant parameters, lipid profile, plasma glucose, and insulin levels and the relative expression of some metabolic genes were assessed. APN caused a significant decrease (P<0.05) in weight gained, body mass index, insulin resistance, plasma glucose, and insulin levels. High-density lipoprotein cholesterol level was significantly increased (P<0.05), while triacylglycerol, cholesterol, low-density lipoprotein, cardiac index, atherogenic index, coronary artery index, and malondialdehyde levels in plasma and liver samples were also significantly decreased (P<0.05) by APN at all experimental doses when compared to the group fed with an HFHF diet only. APN also significantly (P<0.05) upregulated the relative expression of glucokinase, carnitine palmitoyltransferase-1 (CPT-1), and leptin at 400 mg/kg body weight when compared to the group fed with an HFHF diet only. This study showed that APN alleviated dyslipidemia, hyperglycemia, and oxidant effect associated with the intake of a high-fat high-fructose diet.